IPhone Purchase Decisions among Students: A Review of Product Attributes, Lifestyle, and Brand Image - Cherise Cherise; Jarungjung Hutagaol; Evellyn Calista; Nirwana Br Bangun (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the effect of product attributes, lifestyle, and brand image on iPhone purchasing decisions among students of the Faculty of Information Systems at Universitas Prima Indonesia. The study employed a quantitative explanatory approach with a sample of 82 respondents selected from a population of 460 students using the Slovin formula. Data were collected through questionnaires measured on a Likert scale and analyzed using multiple linear regression with SPSS. The results showed that product attributes, lifestyle, and brand image had positive and significant partial effects on purchasing decisions. Product attributes had the strongest effect, followed by brand image and lifestyle. Simultaneously, the three independent variables also had a significant effect on purchasing decisions, with an Adjusted R Square value of 0.581, indicating that 58.1% of the variation in purchasing decisions could be explained by the model. These findings suggest that students tend to consider functional product value, compatibility with their lifestyle, and the strength of brand image when deciding to purchase an iPhone. This study implies that companies should strengthen product quality, maintain a strong brand image, and align marketing strategies with consumer lifestyles in order to increase purchasing decisions.